The Influence of COVID-19 Pandemic on Physical Health–Psychological Health, Physical Activity, and Overall Well-Being: The Mediating Role of Emotional Regulation - Dai, Jianhui; Sang, Xuehui; Menhas, Rashid; Xu, Xia; Khurshid, Sumaira; Mahmood, Sajid; Weng, Yu; Huang, Jiaai; Cai, Yuwei; Shahzad, Babar; Iqbal, Waseem; Gul, Maryam; et al. (Frontiers in Psychology, 2021)
Background: Highly infectious respiratory disease COVID-19 emerged in Wuhan, China, and spread worldwide. Different measures have been adopted worldwide to contain the COVID-19, and these measures have various impacts on health-related quality of life (HRQoL). This study aimed to assess the impact of the COVID-19 pandemic (CP) and lockdown policy on physical health (PH)–psychological health (PsH), physical activity (PA), and overall well-being (OW) in the context of HRQoL, exploring the mediating role of emotional regulation (ER). Method: The current study was conducted in two provincial cities of China. An online survey was conducted in both the cities to collect the data. After quantifying the data, a total of 2,200 respondents data were analyzed through appropriate statistical techniques. Results: The study results indicate that CP was found significantly and negatively related to PH (β = −0.157, t = 9.444, p < 0.001). A significant relationship was found between CP and PsH (β = 0.779, t = 45.013, p < 0.001). The third prediction revealed a significant negative relationship between the CP and OW (β = −0.080, t = 5.261, p < 0.001). The CP and PA had a significant negative relationship (β = −0.047, t = 3.351, p < 0.001). Conclusion: The PH, PsH, and OW of the Chinese people were affected due to the CP and lockdown measures. It is suggested that ER intervention reduces the negative psychological impacts for improving quality of life. ER can function one's sentiments in their social environment effectively for quality of life.